Photo-Ordering and Deformation in Azobenzene-Containing Polymer Networks under Irradiation with Elliptically Polarized Light - Toshchevikov, Vladimir; Saphiannikova, Marina (Processes, 2023)
Azobenzene-containing polymers (azo-polymers) have been a subject of extensive investigations during the last two and half decades, due to their remarkable ability to undergo pronounced alignment and deformation under irradiation with light. The molecular ordering and deformation in azo-polymers of various structures under irradiation with linearly polarized light was described in a series of theoretical works, based on the effect of the reorientation of azobenzene moieties due to the anisotropic character of the photoisomerization processes. In the present study, we generalize the previous orientation approach to describe the photo-alignment and deformation of azo-polymer networks under irradiation with elliptically polarized light. We demonstrate that, in general, the light-induced ordering and deformation have a biaxial symmetry defined by the polarization ellipse. Azobenzene chromophores have a tendency to align along the direction of light propagation, the orientation in the other two directions being dependent of the aspect ratio of the polarization ellipse. This causes deformation of azo-polymer networks along the direction of light propagation, the sign of which (expansion/contraction) is defined by a chemical structure of network strands. Theoretical results are in agreement with experiments and have a practical importance to predict the photo-mechanical response of azo-polymers depending on their structure and on the polarization of light.